Perubahan Lahan Desa Bukian Payangan 6 Tahun Terakhir dengan Metode NDVI - I Wayan Suky Luxiana; Anak Agung Gde Ananditya Prihantara; Ratu Agung Ayu Saraswati Aryawangsa (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
Land changes in an area can be known by analyzing the density of vegetation, the density of vegetation in an area can affect human life and the environment. The purpose of this study is to find out the land changes in Bukian Village in the last ten years using NDVI. The method used in this study with the interpretation of Landsat 8-9 OLI images with NDVI was classified and adjusted through vegetation density. The results of this study where in the last 6 years there has been a reduction in rice fields, plantations and forests of 33.5 Ha and the addition of residential land of 28.2 Ha is due to the increase in population and activities of Bukian Village and the construction of tourism facilities.